O-GlcNAcylation and inflammation: a vast territory to explore - Baudoin, Léa; ISSAD, Tarik (Frontiers in Endocrinology, 2015)
O-GlcNAcylation is a reversible post-translational modification that regulates the activities of cytosolic and nuclear proteins according to glucose availability. This modification appears to participate in several hyperglycemia-associated complications. An important feature of metabolic diseases such as diabetes and obesity is the presence of a low-grade chronic inflammation that causes numerous complications. Hyperglycemia associated with the metabolic syndrome is known to promote inflammatory processes through different mechanisms including oxidative stress and abnormally elevated protein O-GlcNAcylation. However, the role of O-GlcNAcylation on inflammation remains contradictory. O-GlcNAcylation associated with hyperglycemia has been shown to increase NFκB transcriptional activity through different mechanisms. This could contribute in inflammation-associated diabetic complications. However, in other conditions such as acute vascular injury, O-GlcNAc also exerts anti-inflammatory effects via inhibition of the NFκB pathway, suggesting a complex regulation of inflammation by O-GlcNAc. Moreover, whereas macrophages and monocytes exposed to high glucose for a long term period developed a pro-inflammatory phenotype, the impact of O-GlcNAcylation in these cells remains unclear. A future challenge will be to clearly establish the role of O-GlcNAcylation in pro- and anti-inflammatory functions in macrophages.